Cooperative evolution with reward-based heterogeneous tax in spatial public goods games - Li Yue; Huizhen Zhang; Yueyu Sun; Tianbo An; Jingrui Wang (iScience)
Summary: In recent years, incorporating tax mechanisms into evolutionary game theory has become a popular research focus. However, previous studies often failed to simultaneously consider the coexistence of heterogeneity in tax collection and distribution. In this article, we introduce a heterogeneous tax mechanism and apply it to the reward model of the traditional public goods game. Surprisingly, changes in reward costs have little impact on defectors, primarily influencing competition within cooperative strategies. We explain the reason for this phenomenon through the individual’s strategy transfer probabilities. Another important finding is that rewarding cooperators is always available despite their number being few at lower tax rates. It is because when rewarding cooperators face unfavorable situations, global tax becomes a key factor in maintaining their survival. Finally, the robustness of the model is verified.